GE_GERICHTE C/18500/2014 vom 12. Februar 2016 - GE Cour de justice (2016)
CHOSE JUGÉE; EXCEPTION(MOYEN DE DÉFENSE); DÉCISION ÉTRANGÈRE; RECONNAISSANCE DE LA DÉCISION; OBLIGATION D'ENTRETIEN; ENFANT; REVENU HYPOTHÉTIQUE; MINIMUM VITAL | CC.176.1.2; CC.176.3; CC.285